(untitled) (Costa Rican Journal of Guidance & Counseling, 2021)
Today’s society has made multiple changes during the current years, breaking ideological barriers and some stereotypes, within which there is the incursion of women into non-traditional careers for their sex, such as engineering. It is for this reason that the interest arises to conduct this research. With the general purpose of determining the influence of vocational factors in the professional choice of first-level female students of the Engineering in Topography and Cadastre at the National University, to recognize the reason for their choice. This research was carried out using a naturalistic paradigm and a qualitative approach due to the characteristics they possess, among the findings identified it is mentioned that the factor that least influences the vocational choice was the socioeconomic one, the family. Although it is an important element due to the internal dynamics, it does not exert the necessary pressure to intervene in the decision of the students and, nonetheless, there are still stereotypes in society towards women. This work aims to create awareness in readers about the capacity for change. To show a current phenomenon, which is the incorporation of women in spaces with a predominance of men in the academic field and, later, in the workplace.